Theoretical performance simulation of a high pressure agro-forestry swirl nozzle - Taiwo, A.; Oje, K. (International Journal of Agricultural and Biological Engineering, 2012)
Equations of dynamic systems in droplet distribution at high pressure and boundary value flows in the swirl chamber of a swirl nozzle were used in conjunction with momentum equations of forces on moving curved vanes to develop mathematical models. A computer program in C++ language was developed and used to simulate the effect of some flow and geometric parameters, including flow rate, pressure and swirl chamber diameter, on the spray performance of a high pressure agro-forestry swirl nozzle. Each of the three performance parameters of axial flow rate, spray cone angle and output discharge (or performance) coefficient were studied as a function of any two combinations of the nozzle supply pressure, exit orifice diameter and swirl chamber diameter. The study established that the spray cone angle of the discharge flow pattern varied from the minimum value of 40